Emotional and cardiovascular health: the impact of depression on cardiac autonomic activity. (14th October 2021) - Theofilis, P; Oikonomou, E; Lazaros, G; Vogiatzi, G; Tsalamandris, S; Chasikidis, C; Fountoulakis, P; Anastasiou, M; Goliopoulou, A; Mystakidi, V X; Papakonstantinou, M; Christoforatou, E; et al.
Abstract: Background: The coexistence of depression and cardiovascular diseases is frequently accompanied by an increased risk of adverse outcomes. QTc, an indicator of ventricular depolarization and cardiac autonomic activity, has been proposed as a biomarker of this interplay. Purpose: We aimed to investigate the possible association of depression with QTc interval. Methods: Assessment of depressive symptoms was performed in 1637 participants of the cross-sectional Corinthia study with the Zung self-rating depression scale in those younger than 65 years of age (Group 1) and with the geriatric depression scale in elderly individuals (>65 years, Group 2). Moreover, electrocardiogram was performed and measurement of the QT interval was derived after correction for heart rate (QTc) using the Bazett's formula. Abnormal QTc was present when QTc duration exceeded 440 ms. Results: Group 1 individuals classified as having depression had longer QTc duration (No depression: 389.3±27.0 ms vs. Depression: 401.1±32.9 ms, p<0.001) and percentage of abnormal QTc (No depression: 2.0% vs. Depression: 10.8%, p=0.001) (Figure 1, Panels A and B). Elderly individuals had similar values of QTc (No depression: 409.9±29.6 ms vs. Depression: 405.2±46.4 ms, p=0.37) and percentage of abnormal QTc (No depression: 13.2% vs. Depression: 12.3%, p=0.78) irrespective of depression status (Figure 1, Panels C and D). The presence of depression in Group 1 subjects was associated with an increased QTc- by 10.8 ms and with an approximately 7-fold higher prevalence of abnormal QTc duration, even after adjustment for confounders (). Such finding was not detected in elderly individuals (Figure 1, Panel F). Conclusion: Depression might adversely affect ventricular repolarization especially in middle-aged subjects. These findings highlight the interrelationship between emotional and cardiovascular health and the role of depression as a cardiovascular risk factor. Funding Acknowledgement: Type of funding sources: None.